Impact of improved stroke green channel process on the delay of intravenous thrombolysis in patients with acute cerebral infarction during the COVID-19 pandemic: An observational study - Qiwei Wang; Yan Wang; Yongpeng Wang; Qianqian Bi; Quanbin Zhang; Feng Wang (Frontiers in Neurology, 2022)
ObjectiveThis study analyzed the impact of the improved stroke green channel process on the delay of intravenous thrombolysis in patients with acute cerebral infarction under coronavirus disease 2019 (COVID-19) prevention and control measures.MethodsWe included 57 patients from the stroke center of the Seventh People's Hospital of Shanghai University of Traditional Chinese Medicine before the improvement of the stroke green channel process (March–July 2019), as well as 94 patients during the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak (March–July 2020) and 68 patients during the Omicron variant outbreak (March–July 2022) after the improvement of stroke green channel process. The door-to-needle time (DNT), door-to-imaging time (DIT), and door-to-test completion time were compared among the three groups. We analyzed the impact of this process improvement in the emergency green channel during the pandemic on the delay of intravenous thrombolysis.ResultsThis study included a total of 229 patients with acute cerebral infarction who went through the green channel for intravenous thrombolysis (57 in the pre-pandemic group, 94 in the SARS-CoV-2 outbreak group, and 68 in the Omicron outbreak group). The percentages of patients undergoing intravenous thrombolysis in the pre-pandemic, SARS-CoV-2 outbreak, and Omicron outbreak groups differed significantly (19.32%, 22.27%, and 28.94%, respectively, P = 0.029). Compared to the pre-pandemic group, the National Institutes of Health Stroke Scale (NIHSS) score at admission was significantly higher in the Omicron outbreak group (7.71 ± 7.36 in the Omicron outbreak group vs. 5.00 ± 4.52 in the pre-pandemic group) (P = 0.026) but not in the SARS-CoV-2 outbreak group (4.79 ± 5.94 in the SARS-CoV-2 outbreak group vs. 5.00 ± 4.52 in the pre-pandemic group, P = 0.970). Significantly higher proportions of patients undergoing emergency intravenous thrombolysis came to the hospital by ambulance in the SARS-CoV-2 and Omicron outbreak groups compared to the pre-pandemic group (38.6% in the pre-pandemic group, 51.1% in the SARS-CoV-2 outbreak group, and 82.4% in the Omicron outbreak group, P < 0.001). Compared to the pre-pandemic group, the DIT was significantly higher in the SARS-CoV-2 outbreak group (22.42 ± 7.62 min in the SARS-CoV-2 outbreak group vs. 18.91 ± 8.23 min in the pre-pandemic group, P =0.031) but not the Omicron outbreak group (20.35 ± 10.38 min in the Omicron outbreak group vs. 18.91 ± 8.23 min in the pre-pandemic group, P = 0.543). The door-to-test completion time was significantly longer in the SARS-CoV-2 and Omicron outbreak groups compared to that in the pre-pandemic group (78.37 ± 25.17 min in the SARS-CoV-2 outbreak group, 92.60 ± 25.82 min in the Omicron outbreak group vs. 65.11 ± 22.35 min in the pre-pandemic group, P < 0.001); however, the DNT in the SARS-CoV-2 and Omicron outbreak groups did not differ significantly from those in the pre-pandemic group (both P > 0.05).ConclusionDuring the two periods of the COVID-19 outbreak (SARS-CoV-2 and Omicron), after the improvement of the green channel for intravenous thrombolysis, there might be some delay in in-hospital DIT during the SARS-CoV-2 outbreak, however, the in-hospital delay indicator DNT for intravenous thrombolysis were not affected.